Development and validation of a multidimensional organizational dehumanization scale: Evidence from higher education - Semin Kazazoglu; Dilruba Sahin; Cem Oktay Guzeller; Dilek Ilhan-Findikoglu; Fuat Findikoglu (PLoS ONE, 2026)
Organizational dehumanization has become a salient concern in contemporary academic work, particularly in higher education systems shaped by managerial and metric-driven governance. This study aimed to develop and validate a psychometrically robust instrument to assess academics’ perceived organizational dehumanization. Using two independent samples of academics in Türkiye (EFA sample: n = 318; CFA sample: n = 263; total N = 581), we examined the scale’s factor structure, reliability, and validity evidence. Exploratory and confirmatory factor analyses supported a two-factor model reflecting Devaluation and Instrumentality, yielding a final 34-item scale. The model demonstrated acceptable-to-strong fit indices (χ²/df = 2.28; CFI = .99; NFI = .97; RMSEA = .074; SRMR = .045), high internal consistency (α = .93−.96; overall α = .96), and evidence for discriminant validity, with mixed evidence for convergent validity at the subdimension level. Overall, the findings suggest that the proposed scale provides a reliable, multidimensional measure of academics' organizational dehumanization perceptions, validated in a higher education sample, and offers a tool for future research and institutional diagnostics in university contexts.